Legal Protection for Consumers in Online Sales and Purchase Agreements from the Perspective of Commercial Law - Ahmad Baqi; Restu Ari Pratama; Dinda Saskia; Ghina Sukmana; Jumarik (ISNU Nine-Star Multidisciplinary Journal, 2026)
The rapid development of information technology has fundamentally transformed commercial activities, particularly through the growth of online buying and selling transactions conducted via digital platforms. These transactions are legally based on agreements between business actors and consumers, thereby creating civil law relationships governed by commercial and contract law principles. However, in practice, online transactions frequently give rise to legal problems, including breach of contract, non-conformity of goods or services, misinformation, and various forms of consumer loss. These issues highlight the need for effective legal protection mechanisms to balance the unequal positions of consumers and business actors in the digital marketplace. This study aims to analyze the forms and effectiveness of consumer legal protection in online buying and selling agreements from a commercial law perspective. The research employs a normative legal research method using statutory and conceptual approaches, focusing on relevant commercial law principles, consumer protection regulations, and electronic transaction laws. The analysis examines the extent to which existing legal frameworks provide preventive and repressive protection for consumers, particularly in relation to contractual rights, obligations, and dispute resolution mechanisms. The findings indicate that commercial law and related regulations have established a normative foundation for consumer protection in online transactions. Nevertheless, significant challenges remain in their practical implementation, particularly regarding law enforcement effectiveness, regulatory supervision, and the level of public legal awareness. Strengthening institutional enforcement and improving consumer legal literacy are therefore essential to ensure effective consumer protection in the digital trading environment.